2021
DOI: 10.1088/1741-2552/abf590
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for implanting free-floating microdevices into the nervous tissue

Abstract: Objective. Free-floating implantable neural interfaces are an emerging powerful paradigm for mapping and modulation of brain activity. Minuscule wirelessly-powered devices have the potential to provide minimally-invasive interactions with neurons in chronic research and medical applications. However, these devices face a seemingly simple problem—how can they be placed into nervous tissue rapidly, efficiently and in an essentially arbitrary location? Approach. We introduce a novel injection tool and describe a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…We have previously shown that the spatial precision of our injection method was excellent as the microdevice reached within 200 µm of its target location 91% of the time (Khalifa et al, 2021). In this study, all 11 microdevices in all five rats reached their target site.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…We have previously shown that the spatial precision of our injection method was excellent as the microdevice reached within 200 µm of its target location 91% of the time (Khalifa et al, 2021). In this study, all 11 microdevices in all five rats reached their target site.…”
Section: Resultssupporting
confidence: 58%
“…The microdevices were injected using a custom-made novel injection tool described in detail in Khalifa et al (2021). The main components of the injection tool are a 22G (or thin wall 23G) needle, and 350 µm stainless steel cylindrical rod (OrthoTechnology, FL, United States; Figure 2B).…”
Section: Injection Methods and Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The microbead was fully implanted in the sciatic nerve of a rat to confirm its ability to elicit action potentials in axons. Its injection tool and approach are described in detail in (Khalifa et al 2021a ). The main components of the injection tool are a 23G needle and a stainless-steel cylindrical rod, where PEG is used to temporarily affix the microdevice to the tip of the rod.…”
Section: Fully Injectable Microdevices and Injection Strategiesmentioning
confidence: 99%